CROSS PROMOTIONAL STRATEGY IN INCREASING SALES OF FOOD PRODUCTS - Amelia, pingki; Muntaha, Ahmad (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
Promotion is one of the right strategies in delivering communications to consumers. This promotion is one of the activities that can be carried out by companies that are very closely related to obtaining optimal profits. The purpose of this research is to find out and get an overview of the cross-promotion activities carried out by seblak outlets and baso aci champion. This research is descriptive in nature, data collection techniques using the method of observation, interviews, and documentation. The data analysis technique used is interactive analysis techniques, namely data reduction, data presentation, and verification conclusions. Apart from the promotion component, promotional activities also occur between online and offline consumers, namely through word of mouth communication, creating outlets and marketing. through via delivery such as gofood, shopefood, and so on